D retention and material defects probed using Raman microscopy in JET limiter samples and beryllium-based synthesized samples. (27th September 2021) - Pardanaud, C; Kumar, M; Roubin, P; Martin, C; Ferro, Y; Denis, J; Widdowson, A; Douai, D; Baldwin, M J; Založnik, A; Lungu, C; Porosnicu, C; et al.
Abstract: We report on the detection by means of Raman spectroscopy of amorphous beryllium deuteride, BeD2, in magnetron sputtered deposits synthesized in two different laboratories and containing about 20 at% of deuterium. In contrast, this signature has not been found for the JET limiter samples studied coming from the inner, outer or upper limiters, even when coming from a deposition zone of the limiters. We give a way to disentangle that BeD2 signature from other signatures falling in the same spectroscopic range and mainly related to other phenomena. We also analyze the Raman characteristics of the JET sample defects. These results could help in the interpretation of D thermal desorption spectra and in future analyses of JET thick Be deposit divertor tiles.